Risk management for cyber security managers. (Packt Publishing, 2022)
Cyber risk management strategies help decision-makers about the risks associated with it on a day-to-day operational level. A strategized cyber risk assessment can help businesses establish the likelihood of any cyber-related attacks they can be vulnerable to and eliminate them. This course begins with a cursory overview of risks and the different risks an organization can face. We will then delve into the risk management scope and roles. We will also understand the various threats and adversaries an organization can stumble upon. Further, you will learn to identify, assess, and understand the various risk management processes. We will then focus on risk mitigation, avoidance, transference, acceptance, and rejection. Next, you will learn more about information classification, the different security controls, and how to implement them. We will closely examine the different vulnerabilities an organization gets exposed to and third-party cyber risk management. We will understand how ethical hacking and penetration testing can help prevent cyber risks. Upon completing the course, we will acquire comprehensive information about cyber risk management and be able to mitigate cyber risks and develop successful business continuity and disaster recovery plans. What You Will Learn Understand the foundations of risk management in cyber security Learn how to determine and analyze risks Understand how to mitigate, transfer, avoid, and monitor risks Learn how to manage third-party cyber risks effectively Learn ethical hacking/penetration testing to reduce vulnerabilities Understand how to calculate quantitative/qualitative risk analyses Audience This course primarily focuses on information technology or cyber security managers and is designed to help them understand the concepts elaborately. This course is intended to provide comprehensive insight into cyber risk management but not prepare for certifications related to the topic. This short course superficially embarks on the crucial concepts in cyber risk management. If you are new to cyber risk management or want to further your knowledge in this field, being risk manager or cyber security personnel, this course is for you. A basic understanding of cybersecurity is required. About The Author Alexander Oni: Alexander Oni is a bestselling instructor with 70,000 students enrolled in his courses. His passion includes teaching through online courses in an entertaining way. Alex has been teaching online for three years and has created over 25 courses with numerous students registered worldwide. Alex believes we all have one shot at life and should live life to the fullest, constantly stepping out of our comfort zone, visiting places, and trying new things. His success in Udemy has given him financial freedom and the ability to travel and settle anywhere. The author is currently avidly traveling, spending a month in every city and moving to the next. His hobbies include watching movies, sports, and chess.